A review on physicochemical properties and pharmacological activity present in Erythrina variegata plant leaves - S., Elavarasan; K. P. S., Pavithra (International Journal of Basic & Clinical Pharmacology, 2025)
The morphology, pharmacological activity, and phytochemical screening of Erythrina variegata are the briefly outline in the study. A substitute term for E. variegata is also known as Erythrina indica. The plant is capable of reaching an average height of between fifty and sixty feet. Many phytoconstituents, which includes alkaloid substance, tannins, flavonoids, and other resin, protein, saponins and glycosides, have been identified. Terpenoids, triterpenoids, steroids, and phenols are a few examples of secondary metabolites. According to Soxhlet techniques, there are five unique solvent system: methanol, hexane, ethyl acetate, dichloromethane, chloroform, and aqueous solution. Various parts of this plant have been used in traditional medicinal for their analgesic, nervine-calming, antiseptic, antacid antiepileptic, anti-asthmatic, and anti-inflammatory properties. E. variegata plant parts of leaves are used to treat infections produced by bacteria that inhibit or eradicate Pseudomonas and Escherichia (E. coli) bacteria. Its further block both grammeme-positive and grammeme- negative bacteria. E. variegata leaf bark is the main treatment for various diseases in medical systems like siddha (Ayurveda), Unani medicine, and Homoeopathy.